The Health of Older Persons in OECD Countries Is it Improving Fast Enough to Compensate for Population Ageing? - Jacobzone, Stephane (OECD Labour Market and Social Policy Occasional Papers, 1999)
This study extends research on the impact of age-specific disability trends internationally, with a specific emphasis on long-term care needs. It focuses on changing patterns of disability in populations over 65 for a set of OECD countries for which cross-sectional evidence is available for at least two points in time five years or more apart (Australia, Canada, France, Germany, Japan, the Netherlands, Sweden, the United Kingdom and the United States). It analyses the policy implications of trends in health outcomes among older populations, both in terms of financing and with respect to the balance of care between home and institutions. Information related to severe disability, as measured by the ability to carry out activities of daily living, was obtained for the population aged 65 and over, and cross-classified into four age groups and by gender. Two projections were made: one assumes stable rates of disability, and the other reflects the rate of change based on ...